2011
DOI: 10.1177/147323001103900501
|View full text |Cite
|
Sign up to set email alerts
|

Management of Psoriasis in Africa and the Middle East: A Review of Current Opinion, Practice and Opportunities for Improvement

Abstract: Psoriasis is a common, chronic, systemic, inflammatory disease of the skin that is often associated with inflammatory musculoskeletal disease. Psoriasis impacts on affected individuals and on society at many levels, being associated with considerable economic burden and impaired quality of life. This article aims to provide dermatologists and their allied healthcare professionals, particularly those practicing in Africa and the Middle East, with a review of the current understanding of psoriasis, its treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 90 publications
0
25
0
Order By: Relevance
“…The literature search returned a total of 145 publications and 10 of these described patients in Africa or the Middle East. Of these 10 publications, there were 4 research articles ( Table 1 ), 20 23 3 reviews ( Table 2 ), 8 , 24 , 25 2 guidelines (1 from South Africa in 2010 and 1 from Saudi Arabia in 2014; Table 3 ), 26 , 27 and 1 case study (published in Hebrew). 28 Two of the 4 research articles described non-interventional studies and 2 reported data from studies on the safety and efficacy of phototherapy (1 in patients with plaque psoriasis localized to the scalp or palmoplantar areas and 1 in patients ≥65 years of age).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search returned a total of 145 publications and 10 of these described patients in Africa or the Middle East. Of these 10 publications, there were 4 research articles ( Table 1 ), 20 23 3 reviews ( Table 2 ), 8 , 24 , 25 2 guidelines (1 from South Africa in 2010 and 1 from Saudi Arabia in 2014; Table 3 ), 26 , 27 and 1 case study (published in Hebrew). 28 Two of the 4 research articles described non-interventional studies and 2 reported data from studies on the safety and efficacy of phototherapy (1 in patients with plaque psoriasis localized to the scalp or palmoplantar areas and 1 in patients ≥65 years of age).…”
Section: Resultsmentioning
confidence: 99%
“…Population-based studies have estimated the prevalence of PsA in the United States to be 0.25% [95% confidence interval (CI) 0.18-0.31%] [20] and in the United Kingdom to be 0.19% (95% CI 0.185-0.193%) [26]. However, a comparison with African and Middle Eastern populations is not currently possible since the majority of research into PsA has been carried out in Western countries and there are very few published studies on the prevalence and burden of PsA in Africa and the Middle East [5,18], which was evident in our literature search. Consequently, the reported global estimates of incidence and There was a lack of consensus in the use of biologics for the treatment of psoriasis and PsA in clinical practice, which was attributed to low physician awareness, high cost, and non-adherence Conaghan et al [9] Multi-national survey of dermatologists and rheumatologists in the Asia-Pacific region and the Middle East…”
Section: Incidence and Prevalence Of Psa In Africa And The Middle Eastmentioning
confidence: 99%
“…There is a lack of reliable data on the prevalence and burden of PsA in Africa prevalence may not be reflective of this very large and diverse region [5]. Indeed, the lack of local registries, reliable diagnosis, and reporting of PsA has led to the impression that it is relatively rare in Africa and the Middle East, when in fact the burden of the disease is unknown [16]; a similar observation has been reported for rheumatoid arthritis (RA) [27].…”
Section: Incidence and Prevalence Of Psa In Africa And The Middle Eastmentioning
confidence: 99%
See 2 more Smart Citations